OS10.6 Infigratinib (BGJ398) in patients with recurrent gliomas with fibroblast growth factor receptor (FGFR) alterations: a multicenter phase II study. (6th September 2019) - Lassman, A B; Sepúlveda-Sánchez, J M; Cloughesy, T; Gil-Gil, J M; Puduvalli, V K; Raizer, J; De Vos, F Y; Wen, P Y; Butowski, N; Clement, P; Groves, M D; Belda-Iniesta, C; et al.
Abstract: BACKGROUND: FGFR mutations and translocations occur in approximately 10% of glioblastomas (GBMs). FGFR3-TACC3 fusion has been reported as predictive of response to FGFR tyrosine kinase inhibitor therapy both pre-clinically and clinically. Infigratinib (BGJ398) is a selective small-molecule pan-FGFR kinase inhibitor that has demonstrated anti-tumor activity in several solid tumors with FGFR genetic alterations. Therefore, we conducted a phase II trial to test the efficacy of infigratinib in FGFR-altered recurrent GBM (NCT01975701). METHODS: This open-label trial accrued adults with recurrent high-grade gliomas following failure of initial therapy that harbored FGFR1-TACC1 or FGFR3-TACC3 fusions; activating mutations in FGFR1, 2 or 3; or FGFR1, 2, 3, or 4 amplification. Oral infigratinib was administered 125 mg on days 1–21 every 28 days. Prophylaxis for hyperphosphatemia, a common toxicity, was recommended. The primary endpoint was the 6-month progression-free survival (6mPFS) rate by RANO (locally assessed, estimated by K-M method), with a goal of >40%. RESULTS: As of the Sep 2017 data cut-off, 26 patients (16 men, 10 women; median age 55 years, range 20–76 years; 50% with ≥2 prior regimens) were treated, and 24 (92.3%) discontinued for disease progression (n=21) or other reasons (n=3). All patients had FGFR1 or FGFR3 gene alterations, and 4 had >1 gene alteration. The estimated 6mPFS rate was 16% (95% CI 5.0–32.5%); median PFS was 1.7 months (95% CI 1.1–2.8 months); median OS was 6.7 months (95% CI 4.2–11.7 months); ORR was 7.7% (95% CI 1.0–25.1%). The best overall response was: partial response 7.7% (FGFR1 mutation n=1; FGFR3 amplification n=1); stable disease 26.9%; progressive disease 50.0%; missing/unknown 15.3%. The most common (>15%) all-grade treatment-related adverse events (AEs) were hyperphosphatemia, fatigue, diarrhea, hyperlipasemia, and stomatitis. There were no grade 4 treatment-related AEs. Eleven patients (42.3%) had treatment-related AEs requiring dose interruptions or reductions (most commonly hyperphosphatemia). CONCLUSIONS: Infigratinib induced partial response or stable disease in approximately one-third of patients with recurrent GBM and/or other glioma subtypes harboring FGFR alterations. Most AEs were reversible and manageable. Further potential combinations are being explored in patients with proven FGFR-TACC fusion genes and analysis of biomarker data is ongoing.